KAJIAN MODAL SOSIAL PADA KELOMPOK TANI DI DESA TUMANI KECAMATAN MAESAAN KABUPATEN MINAHASA SELATAN (Kelompok Tani Esa Waya dan Kelompok Tani Sinar Mas) - Youdi ., Mamahit; Welson M. Wangke; Nortje M. Benu (AGRI-SOSIOEKONOMI, 2016)
The objective of research is to examine Social Capital based on the elements of norm, network, trust, reciprocity, and values of the Esa Waya and Sinar Mas farmer groups. This research was conducted from May 2016 until July 2016, started from preparation until report compilation. The data used were in the form of primary data and secondary data. This research was carried out with purposive sampling technique. Fifty percent members of the population every farmer group. They are 11 members of Esa Waya group and 8 members of Sinar Mas group. Data analysis was done descriptively, served with using the table and then be interpreted. The result showed that, those elements of norm, network, trust, reciprocity, and values, social capital able to improve the existence and solidarity on the Esa Waya farmer group. The opposite, social capital has been reduced even has no longer on the Sinar Mas farmer group so that Sinar Mas farmer group was not progressed. In addition, the other factor is the age of Esa Waya group younger then Sinar Mas group. The education levels of the Esa Waya group higher than Sinar Mas group.